The Influence Of Competency, Compensation, And Work Discipline On The Performance Of Makassar City Revenue Service Employees - Muh. Arif; Riska Eka Putri Bachtiar (Economics and Digital Business Review, 2024)
This research aims to determine the influence of competency and work discipline on the performance of Makassar City Revenue Service employees." The population in this study were employees at the Makassar City Revenue Service Office with a sample size of 142 people. The method for collecting data in this research is questionnaires and documentation. The data analysis method uses descriptive methods and inferential methods, namely using multiple linear regression statistical methods to measure the influence of competency, compensation, and work discipline on the performance of Makassar City Revenue Service employees. "Based on the F test, Competency and Compensation have a positive and significant effect on the performance of Makassar City Revenue Service employees.",